CHIEF EXECUTIVE OFFICER (CEO) POWER, CEO KELUARGA, DAN NILAI IPO PREMIUM PERUSAHAAN KELUARGA DI INDONESIA - Sudana, I Made; Aristina, Ni Putu Nina (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The development of family firms led to increase the funding requirement for expansion. Family firms can obtain funds from capital market by doing initial public offering (IPO). The aims of this research is to know the influence of CEO power using proxy of CEO voting right, CEO tenure, and CEO interlock on IPO premium, and the influence of family CEO on IPO premium. This research uses 65 samples of family firm in Indonesia during 2001-2014. The result of multiple regression showed that CEO voting right, CEO interlock, and family CEO are positive significantly affect IPO premium. This finding reveal that when investors make investment decision on IPO’s firms, they will evaluate the quality of firm’s CEO. Also, the presence of family CEO increase investor’s valuation on company shares that increase IPO premium.